Comparing Individuals With PPA to Individuals With AD: Cognitive and Linguistic Profiles - Karpathiou, Nomiki; Kambanaros, Maria (Frontiers in Communication, 2022)
Primary Progressive Aphasia (PPA) is a degenerative condition characterized by the progressive loss of language function. In PPA, aphasia is the most prominent deficit at onset. On the other hand, memory deficits are the hallmark of Alzheimer’s disease (AD). The first aim of the study was to establish differences on neuropsychological testing and connected speech production between Greek-speaking individuals with AD and PPA. The second aim was to investigate the executive deficit involvement in the two conditions. 10 individuals with PPA and 9 individuals with AD took part in a comprehensive cognitive-linguistic evaluation. Fifteen demographically matched neurologically healthy adults served as controls. Participants were evaluated using a battery of neuropsychological measures. Quantitative production analysis and acoustic analysis were performed to calculate narrative and temporal measures of the participants’ speech. Participants with PPA differed significantly from participants with AD on linguistic measures. They performed worse on the long frequent sentences’ subtest of the Sentence Repetition Test and they produced fewer narrative and unique words in picture description. They also produced shorter, less elaborated sentences, and made more phonological errors. The two groups did not differ significantly on memory, executive, visuospatial and semantic composite measures. Compared to neurotypical adults, participants with AD were impaired in memory, and executive function. They also exhibited lexical retrieval difficulties, as well as difficulties in linguistic tasks with an increased processing load. Participants with PPA performed within normal limits on the delay conditions of episodic memory measures. However, they too were impaired in executive tasks, especially for short-term memory and verbal fluency. The production of phonological errors, difficulty in repeating long frequent sentences, and the production of simple and short sentences has differentiated participants PPA not only from neurotypical controls but also from participants with AD. No single measure could differentiate the AD group from the other two groups. These findings should be interpreted with caution considering the small sample size.